Survey on data interoperating-oriented authorization technology - LI Ying; LI Xiaodong; FEI Ziyu; PENG Botao (大数据)
Data interoperating over Internet enables cross-domain connectivity and exchange of data, where authorization is a basic mechanism to protect data ownership and ensure data security. The complexity of cross-domain data exchange poses higher requirements for authorization technology in terms of utility and credibility, thus, there is an urgent need to carry out research on authorization technology for data interoperating-oriented. Firstly, the basic concepts and knowledge of authorization technology were briefly introduced, and the technical requirements of data interoperating-oriented for authorization were analyzed. Secondly, the existing authorization technical capabilities were analyzed from there aspects: trust mechanism, permission model, and policy management. Finally, in response to the limitations of existing authorization technology capabilities, some potential research questions were proposed, aiming to provide ideas and references for follow-up research.